2004
DOI: 10.1038/nrg1427
|View full text |Cite
|
Sign up to set email alerts
|

WNT and β-catenin signalling: diseases and therapies

Abstract: WNT signalling has been studied primarily in developing embryos, in which cells respond to WNTs in a context-dependent manner through changes in survival and proliferation, cell fate and movement. But WNTs also have important functions in adults, and aberrant signalling by WNT pathways is linked to a range of diseases, most notably cancer. What is the full range of diseases that involve WNT pathways? Can inhibition of WNT signalling form the basis of an effective therapy for some cancers? Could activation of W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
1,524
0
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,678 publications
(1,563 citation statements)
references
References 106 publications
19
1,524
0
20
Order By: Relevance
“…As increased VEGF-A expression promotes tumoral angiogenesis and subsequent oncogenicity (Ferrara, 2002;Carmeliet, 2003;Ferrara et al, 2003), we analyzed the expression of oncogenic molecules such as Bcl3 and b-catenin, which has been found to be oncogenic when located in the nucleus (Cogswell et al, 2000;Thornburg et al, 2003;Moon et al, 2004;Clevers, 2006). Our results show an important increase in the total amount of both proteins (Figure 1b) and their preferential nuclear localization in the C57-CYLD C/S cells (Figure 3g).…”
Section: Cyld C/s Enhances the Survival Of Malignant Epidermal Cellsmentioning
confidence: 70%
“…As increased VEGF-A expression promotes tumoral angiogenesis and subsequent oncogenicity (Ferrara, 2002;Carmeliet, 2003;Ferrara et al, 2003), we analyzed the expression of oncogenic molecules such as Bcl3 and b-catenin, which has been found to be oncogenic when located in the nucleus (Cogswell et al, 2000;Thornburg et al, 2003;Moon et al, 2004;Clevers, 2006). Our results show an important increase in the total amount of both proteins (Figure 1b) and their preferential nuclear localization in the C57-CYLD C/S cells (Figure 3g).…”
Section: Cyld C/s Enhances the Survival Of Malignant Epidermal Cellsmentioning
confidence: 70%
“…Remarkably, it has been reported that Ab neurotoxicity induces the expression of Dickkopf 1 (Dkk1) (Caricasole et al, 2004), which may further antagonize Wnt presentation to its complex receptor. All together the data indicate that the activity of Wnt signaling components is compromised in AD brains and thus underlies Ab generation/toxicity/deposition and tau hyperphosphorylation, major pathological hallmarks of this neurodegenerative condition (De Ferrari and Inestrosa, 2000;Mudher and Lovestone, 2002;Caricasole et al, 2003;Moon et al, 2004).…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 96%
“…The Wnt pathway plays an important role in cancer (Polakis, 2000;Moon et al, 2004) and thus it is not surprising that Wnt modulators, including Dkks, are also involved.…”
Section: Dkks and Cancermentioning
confidence: 99%
“…Wnts are an evolutionary conserved family of growth factors, whose signaling is involved in numerous processes in development, in the adult and in disease (Cadigan and Nusse, 1997;Moon et al, 2004;Cadigan and Liu, 2006). Wnts are subject to negative and positive regulation by a wide range on effectors that act either intracellularly to modulate components of the signal transduction machinery, or extracellularly to modulate ligand receptor interactions.…”
Section: Introductionmentioning
confidence: 99%